Transparansi Anggaran Publik Dan Implikasinya Terhadap Efisiensi Pengeluaran Pemerintah Daerah - Miranda Mustika; Wahyu Afdillah; Rika Sartika; Wahjoe Pangestoeti (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This study aims to examine the relationship between public budget transparency and local government expenditure efficiency in the context of accountable and participatory fiscal governance. Using a descriptive-qualitative approach, data were collected through documentation and literature review from reputable sources. The findings indicate that budget transparency, as reflected in the availability of public documents, citizen participation, and digital oversight, significantly contributes to enhancing the efficiency of public spending. Expenditure efficiency is assessed by comparing planning, budget realization, and output achievement. Further analysis reveals that transparency not only directly affects efficiency but is also reinforced by implementation quality and public engagement. These findings align with previous studies that emphasize the positive correlation between information openness and fiscal efficiency at the regional level. Therefore, transparency policies must be supported by the development of information systems, public budget literacy, and strong bureaucratic commitment.